2010
DOI: 10.1177/1470320310379065
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in AT1 and AT2 receptor-protein expression in rats

Abstract: It has long been known that angiotensin type-1 receptors (AT1R) play a critical role in sympathetic regulation, cardiovascular activity, and hormone secretion under physiological and pathological states. On the other hand, the functional significance of angiotensin type-2 receptors (AT2R) is poorly understood. In a recent study we demonstrated that, in rats with chronic heart failure, AT1R protein expression was increased but AT2R expression was decreased in the rostral ventrolateral medulla (RVLM). This imbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 50 publications
4
19
5
Order By: Relevance
“…35,36 In the present study, we observed that AT 2 R expression is higher in females compared to males, consistent with the reports in the brain, kidney, and liver. 1214 However, in contrast, spontaneously hypertensive rats (SHR) showed no sex-dependent differences in AT 2 R expression in aorta and mesenteric arteries. 17 The reason for the apparent discrepancies between the above study and the present study is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 In the present study, we observed that AT 2 R expression is higher in females compared to males, consistent with the reports in the brain, kidney, and liver. 1214 However, in contrast, spontaneously hypertensive rats (SHR) showed no sex-dependent differences in AT 2 R expression in aorta and mesenteric arteries. 17 The reason for the apparent discrepancies between the above study and the present study is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
“…It has long-been assumed that the expression and function of AT2R predominates during development, while that of AT1R prevails during adulthood (Nuyt et al 1999; Yu et al 2010). As a consequence, the role of AT2R in adults has often been over-looked.…”
Section: Discussionmentioning
confidence: 99%
“…This likely stems from a number of reports that have indicated that AT2R expression predominates during development, while the expression of AT1R predominates during adulthood (Grady et al 1991; Ichiki and Inagami 1995; Nuyt et al 1999; Yu et al 2010) . Nonetheless, there are lines of evidence indicating that the brains of adult rodents densely express functional AT2Rs (Gao et al 2012; Hauser et al 1998; Lenkei et al 1996; Lenkei et al 1997) and that AT2R activation, in many instances, counteracts AT1R activation (Sumners et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…29 In addition, in heart failure rats with chronic elevation of pro-inflammatory cytokines, COX-1 was not altered but COX-2 was increased in the PVN. 41 A recent study also suggests that systemic inflammation activates microglia in RVLM to induce COX-2-dependent neuro-inflammation leading to an increase in oxidative stress that contributes to neurogenic hypertension. 42 Together, these studies highlight the importance of COX expression in the manifestation of a variety of disease conditions including neurogenic hypertension.…”
Section: Discussionmentioning
confidence: 99%